2016
DOI: 10.1108/jsm-04-2014-0117
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of customers’ intimacy perceptions on the trust-commitment relationship

Abstract: Purpose This paper aims to draw from intimacy theory in examining the mediating effects of interactive communication and social bonds on the trust–commitment relationship. Design/methodology/approach The study is conducted in the professional services context. Qualitative and quantitative data are gathered from respondents engaged in attorney–client and real estate–client relationships. Unstructured, in-depth interviews are first conducted for use in model development. Study hypotheses are examined and media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 86 publications
9
77
0
2
Order By: Relevance
“…Thus, when customers consider the service provider trusty, the possibility of sharing germane information to foster the sustained progress of the relationship is high. In line with this, research has found that trust promotes interactions between customers and service providers (Ballantyne, 2006;Ponder et al, 2016). It has also been established that a positive relation exists between trust and information sharing (Chai & Kim, 2010;McLeod, 2008).…”
Section: Trust In Service Provider and Cementioning
confidence: 85%
See 2 more Smart Citations
“…Thus, when customers consider the service provider trusty, the possibility of sharing germane information to foster the sustained progress of the relationship is high. In line with this, research has found that trust promotes interactions between customers and service providers (Ballantyne, 2006;Ponder et al, 2016). It has also been established that a positive relation exists between trust and information sharing (Chai & Kim, 2010;McLeod, 2008).…”
Section: Trust In Service Provider and Cementioning
confidence: 85%
“…Similarly, trust is explained as the belief that the other party will act or perform in a socially responsible way and thus will meet the trusting party's expectations devoid of taking any advantage of its vulnerabilities (Gefen, 2000). Accordingly, trust enables customers to share personal information based on a belief that the information will stay confidential, pay for goods and services, and act on advice (Ponder et al, 2016). When the service provider is regarded as trusty by customers, there is a higher chance that they will share germane information to see to it that the relationship continues to grow and develop (Cazier et al, 2007;Chai & Kim, 2010).…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted, obtaining customer satisfaction and attraction is one of the most important and essential business plans and also progress in the business process and earnings (Boateng and Narteh, 2016). It is therefore clear that retaining customer loyalty and attracting other customers is the key to successful business (Ponder et al, 2016). Major marketing techniques, and especially mixed marketing, are based on the 3/8 principles of competition, attraction and selection of target society.…”
Section: Introductionmentioning
confidence: 99%
“…While the non-financial performance of organisation was obtained through executing the proper business function in order to give quality customer services (Murby & Gould, 2005). On the other hand, the impact of customer intimacy with organizational performance can rely oncommitment and trust (Yim, Tse, & Chan, 2008;Canning & Hanmer-Lloyd;Morgan & Hunt, 1994;Ponder, Holloway, & Hansen, 2016), information disclosure (Liang, Li, & Turban, 2009), relationship commitment levels (Bugel, Verhoef, & Buunk, 2011), repurchase intentions (Fernandes, Proenca, & Ramboca, 2013;Olaru, Purchase, & Peterson, 2008;Sedianingsih & Prasetyo, 2016), and customer induced word-of-mouth (Villanueva, Yoo, & Hanssens, 2008;Bijmolt et al, 2010).…”
Section: Customer Intimacy and Organisational Performancementioning
confidence: 99%